Precious Forests - Precious Earth 2015
DOI: 10.5772/61015
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and Underlying Causes of Illegal Timber Trade in Uganda

Abstract: Uganda has policies and laws that can foster legal timber trade. This chapter reviews the key sources of timber and current production channels in Uganda. It describes policies and laws governing timber trade and challenges encountered in the quest for legal timber trade. We also show the underlying and proximate causes of illegal timber trade and its impacts on livelihoods, environment, and economy. The sources of timber in Uganda were previously the government-owned forest plantations and natural forests whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Our review articulates that both Tropical Rainforest Reserves (Low and well-stocked) showed a linear significant decline in the number of hectares between 1990-2020 with 10% being Tropical Rainforest Reserves Reserve lowstocked and 12% as Tropical Rainforest Reserves Reserve well-stocked which has an impact on the occurrence and diversity of medicinal plant species. The reason for such a drastic decrease in the forest cover could be a due increase in population which leads to the demand for forest products such as hardwood timber and fuel wood that provides a source of energy for cooking (Turyahabwe et al, 2015;UBOS, 2020). In addition, other scholars have indicated that the decline in the forest cover is attributable to the conversion of more forest land to crop farming and animal rearing which corroborate with our findings of the review (Waiswa et al, 2015;Josephat, 2018;Mwangi et al, 2018;Twongyirwe et al, 2018).…”
Section: The Trend Of Deforestation In Tropical Rainforest Reserves I...mentioning
confidence: 99%
“…Our review articulates that both Tropical Rainforest Reserves (Low and well-stocked) showed a linear significant decline in the number of hectares between 1990-2020 with 10% being Tropical Rainforest Reserves Reserve lowstocked and 12% as Tropical Rainforest Reserves Reserve well-stocked which has an impact on the occurrence and diversity of medicinal plant species. The reason for such a drastic decrease in the forest cover could be a due increase in population which leads to the demand for forest products such as hardwood timber and fuel wood that provides a source of energy for cooking (Turyahabwe et al, 2015;UBOS, 2020). In addition, other scholars have indicated that the decline in the forest cover is attributable to the conversion of more forest land to crop farming and animal rearing which corroborate with our findings of the review (Waiswa et al, 2015;Josephat, 2018;Mwangi et al, 2018;Twongyirwe et al, 2018).…”
Section: The Trend Of Deforestation In Tropical Rainforest Reserves I...mentioning
confidence: 99%
“…CBFM has been established in several other countries e.g. Botswana and Namibia [38], Zambia [39], Vietnam [40], Nepal [41], India [42], Philippines [43], USA [44], Mexico [45], China [46], Malawi, Kenya and Uganda [47,48]. CBFM is widely considered as a management strategy aimed at reducing poverty, conserving natural resources and promoting good governance and decentralization [49].…”
Section: The Role Of Community-based Organizationsmentioning
confidence: 99%
“…In comparison to metals, glass and plastics, wood is an exceptionally versatile material, requires little energy across its life cycle, present lighter carbon footprint, are easy to finish and have higher insulation rating [2]. The dynamic nature of the building environment in Uganda poised by high population growth, urban agriculture and massive industrialization has led to a rise in the demand for wood [3,4]. Consequently, many unregulated industries have sprung up in Ugandan wood industry, leaving several environmental footprints [5][6][7].…”
Section: Introductionmentioning
confidence: 99%